TINGKAT KEPATUHAN PENGGUNAAN ALLOPURINOL 100 MG TERHADAP KUALITAS HIDUP PASIEN GOUT DI DESA DONOREJO, KARANG TENGAH, DEMAK, JAWA TENGAH - Ayu Aprilia Atika Sari; Eko Retnowati; Fahrudin Arif (Nusantara Hasana Journal, 2025)
Gout is a metabolic disorder that results in chronic accumulation of excess uric acid in the blood/hyperuricemia, resulting in the accumulation and formation of uric acid crystals abnormally in the intra-articular space. One of the risk factors that can cause an increase in the incidence of morbidity and mortality of gout sufferers is patient non-compliance in taking anti-gout medication. Anti-gout treatment must be carried out routinely to improve the patient’s quality of life. This research to analyze the level of compliance with the use of allopurinol 100 mg on the quality of life of gout patients in Donorejo Village, Karang Tengah, Demak, Central Java. This study is a non-experimental observational study with a cross-sectional research approach. The sample in this study were gout sufferers in the last 3 months, namely June - August 2025 in Donorejo Village, Karang Tengah, Demak, Central Java, namely 105 respondent samples. The sampling technique in this study used a total sampling approach. The data used in the study were primary data in the form of MMAS-8 and WHOQOL-BREF questionnaires, as well as secondary data in the form of medical records of gout patients. Bivariate analysis was performed using the Chi-square (x2) test. Post-test medication adherence showed that the majority of respondents had a high level of medication adherence, with 77 respondents (73.3%). The post-test Chi-square test obtained a P-value of 0.000, indicating that Ho was rejected and Ha was accepted. This indicates a relationship between adherence to 100 mg allopurinol and the quality of life of gout patients in Donorejo Village, Karang Tengah, Demak, Central Java. The Odd Ratio value obtained was 57.061, indicating that adherence to 100 mg allopurinol in compliant gout patients had a 57.061 times better quality of life than non-compliant gout patients.